Facile synthesis of an Al-doped carbon-coated Li4Ti5O12 anode for high-rate lithium-ion batteries. Issue 81 (15th August 2016) - Yin, Pei-Sin; Peng, Hao-Ting; Xiao, Yaoming; Lin, Tsung-Wu; Lin, Jeng-Yu
Abstract : Sol–gel synthesized LTAO/C composites demonstrated capacity retention of 97.9% at 20C after 100 cycles. Abstract : In this current work, Al-doped carbon-coated Li4 Ti5 O12 (LTAO/C) composites were firstly synthesized via a facile sol–gel method, and subsequently employed as anode materials for high-rate lithium-ion batteries. According to extensive material characterization including X-ray diffraction spectroscopy, high-resolution transmission microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy, LTAO/C composites were successfully not only included with an Al dopant, but also coated with a uniform carbon layer. On the basis of the synergistic effect of the Al-doping and carbon-coating, the resultant LTAO/C electrode displayed superior rate capability and cycling stability. The LTAO/C electrode demonstrates impressive capacity retention of 85.3% at 20C with respect to the discharge capacity at 1C. Additionally, the LTAO/C electrode still retained 97.9% of its initial capacity even after 100 charge/discharge cycles. These results signify that the LTAO/C electrode can be potentially considered as one of the promising anode materials for high-rate lithium-ion batteries.